Professionalization and Proletarianization: Medicine, Nursing, and Chiropractic in Historical Perspective - Coburn, David (Labour/Le Travailleur, 1994)
Two separate theoretical streams touch on the fate of workers and their work, class and 'occupations and professions'. Analysis of the historical development of three interrelated occupations, medicine, nursing, and chiropractic, indicates that medicine is losing control over the health care division of labour. Whether or not one sees processes of proletarianization, however, depends upon whether one is examining a particular occupation or a set of occupations within a particular work domain. The analysis indicates that the struggles amongst occupations themselves contributes to proletarianization.